2014
DOI: 10.4081/vsd.2014.5416
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of simultaneous infection with E. coli O2 and H9N2 influenza virus on inflammatory factors in broiler chickens

Abstract: This study was conducted to evaluate the effect of experimental infection with Escherichia coli O2 and H9N2 influenza virus on inflammatory factors in broiler chickens. A total of 120 oneday-old Cobb broiler chicks were divided randomly to 6 groups. Inoculation program with 10 9 EID50/bird of the A/Chicken/Iran/772/1998 (H9N2) virus and 10 9 CFU/mL/bird of E. coli O2 was carried out as follows: the chicks in group 1 were inoculated with virus and bacteria simultaneously on day 26, group 2 received virus on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Our observation in both backyard and commercial broiler flocks confirms a bidirectional synergistic effect between these concurrently interacting respiratory pathogens in which each pathogen augment pathogenesis of the other one. These bidirectional interactions explain the resulting severe clinical outcomes and higher MR, which coincide with the results of Dadras et al and Mosleh et al [15,30]. E. coli infection before, after, or concurrently with LPAIV (H9N2) infection could exacerbate the adverse effects of the LPAIV (H9N2).…”
Section: Viral/bacterial Interactionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our observation in both backyard and commercial broiler flocks confirms a bidirectional synergistic effect between these concurrently interacting respiratory pathogens in which each pathogen augment pathogenesis of the other one. These bidirectional interactions explain the resulting severe clinical outcomes and higher MR, which coincide with the results of Dadras et al and Mosleh et al [15,30]. E. coli infection before, after, or concurrently with LPAIV (H9N2) infection could exacerbate the adverse effects of the LPAIV (H9N2).…”
Section: Viral/bacterial Interactionsupporting
confidence: 78%
“…AIV of H9N2 subtype has been endemic in poultry in Asia and the Middle East [13,14]. It is clear that IBV infection maximized the pathogenicity and extended the period of H9N2 AIV shedding in chickens [15,16], increasing MR and economic losses, possibly due to mixed infection, and interaction with other respiratory pathogens [2,12,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complement is thought to be involved in host defense of AIV; however, the extent of complement activation may depend on AIV subtype (O'Brien et al 2011). Markers of acute phase responses (e.g., Hp) increase with LPAIV infection in chickens (Sylte and Suarez 2012;Dadras et al 2014). Lymphocytes are essential in controlling LPAIV infection in birds (e.g., reduce viral shedding; Suarez and Schultz-Cherry 2000), whereas heterophils play important roles in the initial replication and dissemination of HPAIV (Pantin-Jackwood and Swayne 2009).…”
Section: Lpaiv Infection and Immunological Indicesmentioning
confidence: 99%
“…It is almost one decade that the Middle East and Asian countries are facing frequent outbreaks of H9N2 infection [ 4 , 5 ]. Mixed infection or coinfection of H9N2 AIV with other respiratory pathogens is one of the possible explanations for increasing the economic losses of H9N2 infection in commercial broiler chickens[ 6 , 7 ]. It was reported that infectious bronchitis virus (IBV) infection increased the pathogenicity and extended the period of H9N2 AIV shedding in broiler chickens [ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%